Notions of popular culture in cultural policy: a comparative history of France and Britain - Looseley, David (International Journal of Cultural Policy, 2011)
The Devlin and Hoyle report, Committing to culture: arts funding in France and Britain, argues that the cultural policies of these two European neighbours have been steadily converging since the mid‐1990s but that their social and economic contexts are now quite different (e.g. youth unemployment, GDP, disposable income). The paper addresses this convergence‐within‐divergence by comparing how policy discourses have conceptualised popular culture in the two countries. It investigates the hypothesis that, in both, an engagement with popular culture has in fact been an important driver of change, albeit at different times and with different taxonomies. And it asks what light this comparison might shed on cultural policy thinking in the twenty‐first century.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2010.541907
Keywords: France; UK; cultural policy; history; popular culture

‘Guys! Stop Doing It!’: Young Women's Adoption and Rejection of Safety Advice when Socializing in Bars, Pubs and Clubs - Brooks, Oona (The British Journal of Criminology, 2011)
Concern about the increase in alcohol consumption amongst young women, drink spiking and drug-assisted sexual assault have culminated in a renewed focus on safety advice for young women. This paper examines young women's responses to safety advice, and their associated safety behaviours, by drawing upon interview and focus group data from a qualitative study with 35 young women (18–25 years) in relation to their safety in bars, pubs and clubs. The findings reveal that young women's behaviours were complex and contradictory in that they resisted, adopted and transgressed recommended safety behaviours. This raises interesting questions about both the practical and the theoretical implications of contemporary safety campaigns, challenging the prevailing focus on women's behaviour and the gendered discourse invoked by such campaigns.

Negotiating the gay male stereotype in ballet and modern dance - Polasek, Katherine M.; Roper, Emily A. (Research in Dance Education, 2011)
Dance, ballet and modern in particular, is culturally defined as a feminine activity in the United States. The purpose of the present study was to examine the experiences of professional male modern and ballet dancers in the United States. Semi-structured interviews were conducted with 12 current professional ballet and modern dancers. We examined the ways in which the dancers initially became involved in dance, any support or opposition they may have confronted, and the ways in which they negotiated the stereotypical assumptions surrounding men’s involvement in dance. Four emergent themes are discussed: (1) exposure to and entrance into dance; (2) the gay stereotype; (3) negotiating the gay stereotype; and (4) homophobia within the dance community. The social significance of this study is rooted in the ways in which our culture constructs gender, the body, and movement, restricting both males and females from using and exploring their bodies in ways not deemed gender-appropriate. Attention is also given to the ways in which we can create and nurture meaningful experiences for a greater number of individuals.
Keywords: Bibliographie; Nettoyer; gay men; homophobia; male dancers; masculinity

A Safe Education for All: Recognizing and Stemming Harassment in Music Classes and Ensembles - Carter, Bruce Allen (Music Educators Journal, 2011)
This article addresses the pervasiveness of harassment in schools in the United States and presents ways to recognize and stem bullying in music classrooms. Music educators are in a unique position to recognize atypical behaviors in their students. Music educators who teach middle and high school ensembles often retain the same students in their classrooms over the course of many years. Because of the unique nature of the ensemble experience, coupled with the opportunity for extended instruction, music teachers can closely monitor the well-being of their students. However, music teachers should understand how difficult it may be for students who have been harassed to come forward with information about harassment. Sometimes harassment is overt and easy to recognize (e.g., name-calling, inappropriate gestures, graffiti). However, harassment can also occur in contexts that are not readily recognized but are just as hurtful. When students observe teachers taking a stand against bullying and harassment, they recognize the intention for a safe classroom. When students feel safe, they are more likely to ask questions and engage in class in dynamic and meaningful ways—both musically and nonmusically. Only when students feel safe can they learn. Music teachers need to gain a further understanding of various forms of harassment and further consider their role in creating a welcoming and secure environment.
Publisher: SAGE Publications Inc
Keywords: Bullying; Harassment; Music classrooms; Myriam

Attouchements sexuels sur une élève : Romuald Pavy plaide coupable (Radio-Canada, 2011)
Le professeur de danse Romuald Pavy a plaidé coupable mardi matin à des accusations d'attouchements sexuels sur l'une de ses élèves.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Music festival sponsorship: between commerce and carnival - Anderton, Chris (Arts Marketing: An International Journal, 2011)
Purpose – This paper aims to examine the cultural heritage of outdoor rock and pop music festivals in Britain since the mid‐1960s, and relates it to developments in, and critiques of, corporate sponsorship in the contemporary music festival sector. Design/methodology/approach – The paper uses extant research materials to construct an account of British music festival history since the mid‐1960s. It then draws upon Bakhtin's concept of the carnivalesque and the literature on sponsorship, experiential marketing and branding, in order to understand critiques of corporate sponsorship and the changing nature of the sector. Findings – Outdoor rock and pop music festivals were dominated by the ideologies of a “countercultural carnivalesque” from the late 1960s until the mid‐1990s. In the 1990s, changes in legislation began a process of professionalization, corporatization, and a reliance on brand sponsorships. Two broad trajectories are identified within the contemporary sector: one is strongly rooted in the heritage of the countercultural carnivalesque, while the other is more overtly commercial. Research limitations/implications – It is argued that experiential marketing and brand activation are key methods for achieving a balance between the competing aspects of commerce and carnival. Hence, festival organisers and sponsors need to understand the history of the sector and of their own events and attendees in order to use corporate sponsorship more effectively. Originality/value – This paper adds historical and theoretical depth to the debate between commerce and carnival within the music festival sector, and makes connections between cultural theory and the literature on sponsorship and branding.
Publisher: Emerald Group Publishing Limited
Keywords: Bakhtin; Branding; Carnivalesque; Counterculture; Music festivals; Sponsorship; United Kingdom

Popular Music and the State in the UK. Culture, Trade or Industry? by Martin Cloonan - Laing, Dave (Popular Music, 2011)

Grunge, Riot Grrrl and the Forgetting of Women in Popular Culture - Strong, C. (2011)
Semantic Scholar extracted view of "Grunge, Riot Grrrl and the Forgetting of Women in Popular Culture" by C. Strong